Improving rotational stability and enhancing efficiency with variable inertial flywheels and magneto-rheological fluids - Salam, Syed Munimus (AlamBiblio Publishers, 2024)
Variations in the rotational speed of a flywheel are naturally resisted by the moment of inertia. A high moment of inertia must be maintained to minimize angular velocity variations. Conversely, a significant moment of inertia makes it difficult to start spinning machines. A flywheel with a variable moment of inertia has been suggested to solve this issue. Although fluctuations between the masses' radii across the flywheel's axis may be used to approximate true inertia, the variable inertial flywheel's (VIF) control mechanisms are somewhat complex. Magneto-rheological (MR) Fluids can be utilized to avoid the complexity of the VIF. The applied device parameters determine the design and construction of the VIF system using a relatively simple control technique. To determine the relation between the semi-active VIF control system and the input parameters of a rotating electrical machine to decrease energy losses, adequate data from a VIF coupled with an induction motor (IM) system is gathered in this study. An analysis was done on the system, and the outcome showed a possible improvement in the performance of IM. This study significantly reduces power consumption and smooth speed build-up possibility for the proposed system.